Pembelajaran Luar Kelas, Aplikasi Pembelajaran AKIK - Lailatul Zahroh (Halaqa: Islamic Education Journal, 2017)
Learning activities in formal schools are experiencing saturation. Standardized learning process routines no longer prioritize the creative ideas of every student because everything must be linearly patterned in the classroom. Learning outside the classroom as a new alternative in improving knowledge in the achievement of human quality. Learning outside the classroom does not simply move the lessons out of the classroom, but is done by bringing students together with nature and performing some activities that lead to the realization of changes in students' behavior toward the environment through stages of awareness, understanding, concern, responsibility and action or behavior. AKIK Learning (Active, Creative, Inspirational and Communicative) is a learning activity that emphasizes student activeness, teacher creativity that stimulates students' creativity, inspires students to continue to learn and apply it in real life everyday, and demands students to be able to communicate the learning result both orally and in writing.